Socialization on the Importance of Serving Data Privacy and Security in the Digital Age - Sutriawan; Khatimah, Nur Husnul; Gufran (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
In the current big data era, the growth of information has shown a very rapid and significant increase. The dissemination of information in the digital era through short messages, voice calls, and updating information on social media and others is something that is commonly done by humans, making it possible for people to connect. Privacy issues are often associated with personal data, user data must be kept confidential, user identity must be protected or user actions must not be randomized, must ensure proper protection for users because of that privacy is not an easy thing to maintain. This Community Service Activity is expected to be able to increase awareness among students, especially SMK 2 Dompu, and the community in general about the importance of maintaining privacy in the current digital era, realizing that social media users are currently increasingly widespread, awareness about data security must be increased because it can have a positive impact as well as impact negative for the user. The spread of data on social media can trigger various cybercrimes that affect each user because there are many crimes that we often encounter, such as cyberbullying, cyberstalking, and various other types of crimes. If you don't increase self-awareness to protect and secure data, then data on social media can be misused by irresponsible parties.